Ruin Probability Model for Disaster Insurance Companies: A Systematic Literature Review - Saefullah, Rifki; Riaman, Riaman; Sukono, Sukono (UIN Sumatera Utara, 2025)
Ruin probability modelling is a crucial aspect for insurance companies that is very important and urgent to maintain the company's solvency. Ruin probability modelling helps identify insolvency risks, so companies can take timely preventive measures before it is too late. This research will present a systematic literature review (SLR) using a bibliometric analysis approach with the support of VOSviewer software, utilising the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. The data sources used in this study came from 3 databases, namely Scopus, ScienceDirect and Dimensions, which resulted in 9 articles relevant to the topic under study. The results identified research gaps that could be an opportunity for future exploration. This research is expected to provide academic and practical contributions in developing ruin risk mitigation strategies in disaster insurance companies facing natural disaster uncertainty.